2014
DOI: 10.1021/jm4016069
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of a Unique Heparin Mimetic Hexasaccharide for Structure–Activity Relationship Studies

Abstract: To date, the structure-activity relationship studies of heparin/heparan sulfate with their diverse binding partners such as growth factors, cytokines, chemokines, and extracellular matrix proteins have been limited yet provide early insight that specific sequences contribute to this manifold biological role. This has led to an impetus for the chemical synthesis of oligosaccharide fragments of these complex polysaccharides, which can provide an effective tool for this goal. The synthesis of three heparin mimeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…The new glycopolymers were then screened for their inhibition of heparanase using an in vitro TR-FRET assay against fluorescence-labeled heparan sulfate to test the effect of increased carbohydrate density and better mimicry of HS chains (diantennary vs monoantennary) 48 along with control glucosamine monosaccharide 33 and disaccharide 34 , as well as oligosaccharides 35 and 36 (Figure 5). 8790 Glucosamine 33 bearing the sulfate group at C(6)- O and C(2)- N positions will be used to determine whether the glucuronic acid (GlcA) is important for inhibition against heparanase.…”
Section: Resultsmentioning
confidence: 99%
“…The new glycopolymers were then screened for their inhibition of heparanase using an in vitro TR-FRET assay against fluorescence-labeled heparan sulfate to test the effect of increased carbohydrate density and better mimicry of HS chains (diantennary vs monoantennary) 48 along with control glucosamine monosaccharide 33 and disaccharide 34 , as well as oligosaccharides 35 and 36 (Figure 5). 8790 Glucosamine 33 bearing the sulfate group at C(6)- O and C(2)- N positions will be used to determine whether the glucuronic acid (GlcA) is important for inhibition against heparanase.…”
Section: Resultsmentioning
confidence: 99%
“…CCL2, CCL11, and CXCL2 interact with a hexasacharide displaying a GlcNS6S-IdoA motif, but not with an otherwise similar molecule displaying a GlcNAc6S-IdoA2S motif. These studies also showed the importance of the 6-O-sulfation of the GlcN in high-affinity binding to CXCL12 [125]. Similarly, the chemical synthesis of heparin-like dodecasaccharides showed that a site-specific modification of the terminal GlcN affects a switch between inhibition of CXCL8 and CXCL12 [126].…”
Section: The Structures Recognized By Chemokinesmentioning
confidence: 87%
“…TD4-143-1, which is a selectively sulfated tetrasaccharide containing unsubstituted glucosamine residues, which inhibited heparanase activity and suppressed invasion of breast cancer cells in vitro (163). Although not designed to specifically inhibit just heparanase, a newly synthesized hexasaccharide was considered to possess typical heparanase inhibition profile consistent with LMWHs and fondapariunx (164). Nevertheless, in both instances the anti-heparanase activity would be considered to be modest which perhaps limits the utility of such approaches in terms of preclinical or clinical development.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%